Genus Acronychia An Extensive Review on Phytochemistry and Pharmacological Activities - Son, Ninh T. (Mini-Reviews in Organic Chemistry, 2023)
Background: Acronychia is a genus of medicinal plants that were used traditionally to treat various ailments such as cough, asthma, sores, ulcers, itchy skin, fever, and rheumatism. Acronychia plants have a wide range of distribution, but they are mostly native to India, Siri Lanka, Australia, and Indochina since the 1950s Acronychia plants have been extensively used in phytochemical research and pharmacological examinations. Objective: The goal of this study is to structurally compile almost secondary metabolites from the title plants, as well as coverage of full information on their biomedical actions. Conclusion: Phytochemical profile of this genus is associated with the appearances of various chemical classes, including principal compounds type acetophloroglucinols and alkaloids, as well as other types coumarins, mono-phenols, flavonoids, phytosterols, lignans, xanthenes, and tocopherols. More than one hundred thirty secondary metabolites have been isolated. Naturally occurring acetophloroglucinols represented in both monomers and dimers, and most of them were new in nature. Phytochemical research based on GC-MS identification showed that Acronychia plants should be suitable for the cosmeceutical field and food chemistry due to the high content of volatiles. Acronychia extracts are safe in use, and they are increasingly exploited within pharmacological assays. In agreement with traditional properties, crude plant extracts, fractions, and their isolated compounds are well-known for antimicrobial, antioxidative, antiinflammatory, antiprotozal, antiarrhythmic, antinociceptive, antihistamine, and allelopathic activities, especially in terms of cytotoxicity. A sustainable use program should be established to aid the further studies of these medicinal plants.
Keywords: cytotoxicity